Seismic Velocity Structure in the Area of the 2007, Mw 8.0, Pisco-Peru Earthquake: Implications for the Mechanics of Subduction in the Vicinity of the Nazca Ridge - I. Bernal; H. Tavera (International Journal of Geophysics)
In this study, we present a velocity model for the area of the 2007 Pisco-Peru earthquake (Mw=8.0) obtained using a double-difference tomography algorithm that considers aftershocks acquired for 6 months. The studied area is particularly interesting because it lies on the northern edge of the Nazca Ridge, in which the subduction of a large bathymetric structure is the origin of geomorphological features of the central coast of Peru. Relocated seismicity is used to infer the geometry of the subduction slab on the northern flank of the Nazca Ridge. The results prove that the geometry is continuous but convex because of the subduction of the ridge, thereby explaining the high uplift rates observed in this area. Our inferred distribution of seismicity agrees with both the coseismic and postseismic slip distributions.